2022
DOI: 10.12982/cmjs.2022.053
|View full text |Cite
|
Sign up to set email alerts
|

New species of Cercosporoid on Mango in Thailand

Abstract: Fungi in Cercospora and Pseudocercospora are commonly known as cercosporoid fungi. In the current study, a cercosporoid fungus was isolated from Mangifera indica from Chiang Mai, Thailand. The isolate was identifi ed as Pseudocercospora mangiferae sp. nov. based on morphology and ITS, act, tef1-α and rpb2 multigene phylogeny. Further, this is the fi rst report of a Pseudocercospora species on M. indica in Thailand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Guo et al [ 14 ] reported seven species of Fusarium from leaf spots of mango. Tamakaew et al [ 15 ] established a new species of Cercosporoid fungus associated with mango in Thailand. Yang et al [ 16 , 17 ] reported 20 saprobic fungi that are associated with mango in China.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al [ 14 ] reported seven species of Fusarium from leaf spots of mango. Tamakaew et al [ 15 ] established a new species of Cercosporoid fungus associated with mango in Thailand. Yang et al [ 16 , 17 ] reported 20 saprobic fungi that are associated with mango in China.…”
Section: Introductionmentioning
confidence: 99%